Rethinking Policy Paradigms: From Technocratic Governance to Value-Based and Socially Just Policies - Muhamad Zaenal Abidin; Abd. Muis (DAAR EL-IDARAH: Journal of Islamic Education Management, 2026)
Global educational policies are increasingly dominated by technocratic governance that prioritizes quantitative metrics, standardization, and performative accountability. While structured to elevate quality, this rigid approach inadvertently marginalizes the humanistic, spiritual, and social justice dimensions within faith-based institutions such as madrasahs. This qualitative case study aims to deconstruct the impacts of technocratic governance and propose an alternative framework through the conceptualization of a Vibrant Social-Justice Policy Framework. Data were gathered through in-depth interviews, participatory observations, and documentary analysis involving madrasah leaders, educators, and policy stakeholders. The study focuses on three main trajectories: analyzing the structural distortions of metrics-based regulations, exploring the internalization of value-based policies, and reconstructing socially just educational practices at the grassroots level. The findings indicate that purely technocratic mandates trigger professional alienation among teachers and displace the core spiritual identity of madrasahs. However, through strategic bottom-up value negotiations, madrasahs can successfully integrate spiritual-humanist values and distributive justice into their daily operations. This integration restores pedagogical autonomy and fosters a more inclusive quality ecosystem without compromising administrative relevance. This study contributes a novel theoretical lens to the sociology of Islamic educational policy and offers humanistic regulatory recommendations for policymakers.